Relación entre los programas sociales y la pobreza monetaria del Departamento de Ucayali durante el periodo 2007 – 2021 - Hurtado Chavez de Bocanegra, Olga Paola (2024)
This research analyzes the relationship between social spending, average income and monetary poverty in the Department of Ucayali, Peru, during the period 2007-2021. Using a descriptive and correlational approach, and relying on Spearman's correlation coefficient, the interactions between these key variables are examined to understand their impact on the socioeconomic development of the region. The results reveal a significant negative correlation between spending on social programs and monetary poverty, indicating that an increase in social spending is associated with a decrease in poverty levels. Furthermore, a positive correlation is observed between social spending and average income, suggesting that investment in social programs contributes to income growth. In turn, average income shows a negative correlation with monetary poverty, reaffirming the importance of inclusive economic growth in the fight against poverty. Conclusions emphasize the need for public policies focused on the efficiency and sustainability of social spending, and on the implementation of inclusive and adaptive strategies for equitable and lasting development in Ucayali.